2019
DOI: 10.1002/masy.201800043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Babassu Mesocarp Incorporation on the Biodegradation of a PBAT/TPS Blend

Abstract: The influence of thermoplastic starch (TPS) and babassu mesocarp incorporation on the biodegradation of poly(butylene adipate‐co‐terephthalate), PBAT, PBAT/TPS blend, and its biocomposite were investigated. PBAT/TPS blend (70:30) and its biocomposite containing 20% babassu (i.e., 17:58:25% wt/wt babassu mesocarp/PBAT/TPS system) were prepared by melt blending in a torque rheometer at 150 °C. Samples for biodegradation were obtained by hot pressing. Size exclusion chromatography showed that incorporation of TPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The data underwent one-way analysis of variance (ANOVA) with the Tukey-Kramer multiple comparisons test for 95% reliability, revealing significant differences between the samples [30]. These variations were considered significant when p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…The data underwent one-way analysis of variance (ANOVA) with the Tukey-Kramer multiple comparisons test for 95% reliability, revealing significant differences between the samples [30]. These variations were considered significant when p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the degradation rate of PBAT composites can be significantly accelerated. Giri et al found that as the fiber content of wheat straw in the composites with PBAT increased, their hydrophilicity also increased, thereby enhancing the biodegradability of the composites [18].…”
Section: Introductionmentioning
confidence: 99%